Occupational pensions in Germany: an economic geography - Burger, C (2011)
By the end of the twentieth century, the generous German public pay-as-you-go pension system had been struggling with a serious deficit due to the country’s ageing population. In 2001, the German government enacted the “Riester” pension reform, named after Mr. Walter Riester, the Labour Minister brokering it, which reduced the level of publicly provided pensions, and strengthened the funded occupational and private pillars in order to replace the loss in retirement income. This thesis investigates the role and structure of occupational pensions during the Riester-reform and in its aftermath, using an economic geography perspective. In doing so, it discusses the role of trade unions and employer associations (social partners) in moulding the structure of the occupational system, and investigates the geography of occupational pensions both at employer and at employee level. Empirically, the thesis is based on an in-depth interview with Mr. Walter Riester, and a unique, proprietary data-set of a German occupational pension provider, containing information on 332 thousand employees and over 12 thousand employers. The results show that the internal division of social partners played a critical role in leaving occupational pensions voluntary, but they have been successful in setting standards on the occupational pension market by means of collective bargaining. Employers and employees show systematic spatiotemporal patterns in their pension-related decisions, confirming the importance of local relationships and local contexts in implementing social partners’ measures and in the transformation of the welfare state. It is finally pointed out that the Riester-reform was a part of a gradual transition, which has been reducing employers’ autonomy in order to reinforce the social role of occupational pensions. To achieve that and to catalyse the reform process, employers’ and employees’ risk exposure has been mitigated in the hope that old-age poverty can be avoided.